Any Target Value of LDL-cholesterol before Elective PCI? A study at NICVD on Association of LDL-Cholesterol levels with Myocardial Injury during Elective PCI - Hasan, Md Zahid; Hashem, Sabina; Ahmed, Mohsin; Haque, Md Monsurul; Jahan, Jafrin; Kabir, Md Khairul; Hosen, Md Imam; Shadly, Tausif Amim (Bangladesh Heart Journal, 2023)
Background: Raised LDL cholesterol has already been established as a strong risk factor the for pathogenesis of atherosclerotic plaque leading to coronary heart disease. During PCI procedure, many patients develop peri-procedural myocardial injury due to mainly atherosclerotic plaque disruption, side branch occlusion and distal small vessel embolization which subsequently affects the mortality and morbidity of patients. Objectives: To find out the association of preprocedural LDL cholesterol levels with myocardial injury in elective PCI patients. Methods: This Cross-sectional observational study was conducted at National Institute of Cardiovascular Diseases (NICVD), Dhaka from July 2020 to June 2021. The sample size was 170. LDL cholesterol and troponin-I were measured before the procedure and troponin I was measured 6 hours after PCI procedure. On the basis of pre-procedural cholesterol level, the study population were categorized into two groups: Group I: patients with normal LDL-C level (£70mg/dl) and Group II :patients with raised LDL-C (>70mg/dl). Results: Total 54(31.8%) patients developed peri-procedural myocardial injury, among them 15(19.7%) were in normal LDL-C group and 39(41.5%) were in raised LDL-C group. Elevation of troponin I after PCI was higher in group II than group I patients with statistically significant difference (p<0.001). Multivariate logistic regression analyses showed that raised LDL-C was an independent predictor of PMI (OR 4.71; 95% CI, 2.072- 10.658; p<0.001). There was positive correlation found between pre-procedural LDL-C and myocardial injury (r=0.44, p<0.001) by Pearson’s correlation coefficient test. Conclusion: Pre-procedural raised LDL-C level was positively and independently associated with myocardial injury after elective percutaneous coronary intervention (PCI). Bangladesh Heart Journal 2023; 38(1): 70-80